Research on the supply-demand balance evaluation and driving mechanism of community public service facilities - Jian Chen; Ying Fu; Shenglan Ma; Qiao Chen; Wanqing Zhang; Junlin Huang (PLoS ONE, 2025)
The configuration level of community-level public service facilities is an important indicator for assessing the completeness of the urban public service system, and its spatial equilibrium directly impacts residents’ quality of life. This study takes 400 living circles in Changsha as samples and, based on the theory of “spatial equilibrium,” applies CRITIC method, system coordination model, and geographic detector to systematically evaluate the “supply-demand” equilibrium of community-level public service facilities. The study finds that: (1) The supply of public service facilities exhibits spatial agglomeration characteristics, while the demand distribution is significantly dispersed, with regional heterogeneity in the supply-demand matching; (2) There is a “Matthew effect” in the configuration of facilities, with significant equilibrium differences between the central urban areas and suburban regions; (3) The coverage of bus stops, farmers’ markets, and multifunctional sports fields are key driving factors, and transportation convenience and daily demand satisfaction are the core pathways to improving equilibrium. This study, by constructing a dynamic “supply-demand” adaptation framework, reveals the spatial equilibrium characteristics of community-level public service facilities and provides systematic planning ideas for optimizing urban public service resource allocation.